The Effect of Dietary Fat from Animal Sources on Prevalence of Obesity and Risk of Hepatic Diseases - Rawaa Al-Mayyahi; Manal Al-Hayder; Nadheerah Neamah (International Journal of Nutrition Sciences, 2025)
Background: Obesity is a main risk factor for different health conditions including hepatic diseases. Previous studies suggested that the type and amount of dietary fat can contribute to such diseases. However, studies of dietary fats from different sources on obesity and its related diseases are reasonably sparse. The current work studied the impact of dietary fat of animal sources on weight gain and hepatic dysfunction in experimental rats.Methods: Eighteen female albino rats were assigned to three equal groups of six rats. Animals were fed with standard food supplemented with olive oil and sheep tallow for one month. The activities of liver enzymes, lipid profile and hepatic histopathology were investigated.Results: The sheep tallow could significantly increase the body weight compared to animals fed with standard diet and olive oil. Levels of liver enzymes were remarkably elevated in rats fed with sheep tallow revealing the hyperlipidemic activity of sheep tallow and its detrimental effects on hepatic tissue.Conclusion: The current findings observed that fat from animal sources increased final body weight indicating the incidence of obesity with continuous feeding with fat of animal sources. The sheep tallow diet adversely affected lipid levels and liver enzymes and induced liver histopathological changes as a non-alcoholic fatty liver disease. In contrast, olive oil seems to be well metabolized in the liver reflecting its beneficial effects on health status.